Hours risk and wage risk: Repercussions over the life-cycle - Robin Jessen; Johannes König (Freie Universität Berlin, School of Business & Economics, 2020)
We decompose permanent earnings risk into contributions from hours and wage shocks. To distinguish between hours shocks, modeled as innovations to the marginal disutility of work, and labor supply reactions to wage shocks we formulate a life-cycle model of consumption and labor supply. Both permanent wage and hours shocks are important to explain earnings risk, but wage shocks have greater relevance. Progressive taxation strongly attenuates cross-sectional earnings risk, its life-cycle insurance impact is much smaller. At the mean, a positive hours shock of one standard deviation raises life-time income by 10%, while a similar wage shock raises it by 12%.
urn:nbn:de:kobv:188-refubium-26380-6
Keywords: D31; J22; J31; 330; Earnings Risk; Wage Risk; Labor Supply; Progressive Taxation; Consumption Insurance